A HOLISTIC MODEL IN LEARNING MULTIMEDIA DESIGN DEVELOPMENT - Edy Jogatama Purhita; Dewi Widyaningsih; Edwin Zusrony (Pixel :Jurnal Ilmiah Komputer Grafis, 2020)
Multimedia learning software development requires design methods, development tools, examination models and proficiency in Information Technology systems. It is necessary to formulate a Holistic Method which considers all related aspects in order to guide the quality of good design in designing Multimedia Learning. Implementing the findings of the Holistic Method formulation to build multimedia learning with good design quality. This study formulates the stages of multimedia development which include: Creative Brief, Design, Material Preparation, Compiling, Testing, Distribution. The multimedia software development process will be guided by 15 guiding elements which are grouped into 5 elements, include : content, appearance, utility aspect, user caracter, and didactic. These guiding elements are used to produce good quality learning multimedia designs. The methodology is called Holistic Multimedia Development Model (HMDM).